2018
DOI: 10.1002/ccd.27638
|View full text |Cite
|
Sign up to set email alerts
|

Cost implications of intraprocedural thrombotic events and bleeding in percutaneous coronary intervention: Results from the CHAMPION PHOENIX ECONOMICS Study

Abstract: IPTE and bleeding complications, though infrequent, are associated with substantial increased cost. These complications should be collected in economic assessments of PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…While our study did not evaluate the cost implications of a prolonged cangrelor infusion, sub-analysis of the CHAMPION PHOENIX study revealed that the increased cost of cangrelor may be offset by a reduction in intra-procedural thrombotic events during PCI resulting in lower major adverse cardiac events, mortality, procedural and hospitalization costs, and shorter hospital stays (6). Rates of major and minor bleeding were similar between cangrelor and clopidogrel in this study, but needs further study in the ischemic stroke population who are prone to intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…While our study did not evaluate the cost implications of a prolonged cangrelor infusion, sub-analysis of the CHAMPION PHOENIX study revealed that the increased cost of cangrelor may be offset by a reduction in intra-procedural thrombotic events during PCI resulting in lower major adverse cardiac events, mortality, procedural and hospitalization costs, and shorter hospital stays (6). Rates of major and minor bleeding were similar between cangrelor and clopidogrel in this study, but needs further study in the ischemic stroke population who are prone to intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 89%
“…Given the predictable pharmacokinetics in patients with a wide variety of underlying co-morbidities, it provides an important solution for acute neurointerventions. Randomized clinical trials in interventional cardiology have found that intravenous cangrelor may be a useful and cost-effective substitute for currently used oral antiplatelets (4)(5)(6). Given the differences in patient characteristics, clinical outcomes, and treatment considerations from cardiac patients, we sought to determine the safety and efficacy of using low dose cangrelor infusions in patients with acute ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have found intraprocedural thrombotic events and delays to coronary bypass surgery, which were reduced with cangrelor, to be associated with significant health care costs. 26,27 In conclusion, the reductions in ischemic events, and thus, the overall efficacy seen with cangrelor in this exploratory analysis of CHAMPION PHOENIX occurred early and during the period of time in which patients were being actively treated with cangrelor. These findings affirm the feasibility of the transition strategy for procedural cangrelor to oral maintenance P2Y 12 inhibition and provide evidence that supports the importance of potent platelet inhibition during PCI.…”
Section: Discussionmentioning
confidence: 70%
“…Prior studies have found intraprocedural thrombotic events and delays to coronary bypass surgery, which were reduced with cangrelor, to be associated with significant health care costs. 26,27…”
Section: Discussionmentioning
confidence: 99%